Fibrous dysplasia of the temporal bone: A review of 66 cases. (3rd December 2014) - Frisch, Christopher D.; Carlson, Matthew L.; Kahue, Charissa N.; Pelosi, Stanley; Haynes, David S.; Lane, John I.; Neff, Brian A.; Link, Michael J.; Driscoll, Colin L. W.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Fibrous dysplasia is a condition of nonmalignant osseous change and may occur in a monostotic or polyostotic pattern, the latter potentially being associated with McCune‐Albright syndrome. Symptoms are highly variable and dependent upon lesion location and size. Study Design Retrospective review. Methods Consecutive subjects with fibrous dysplasia of the temporal bone were evaluated between 2000 and 2013 at two tertiary academic referral centers. Main outcome measures included disease presentation, diagnostic evaluation, management strategy, and outcome. Results Sixty‐six patients with fibrous dysplasia of the skull were found to have involvement of the temporal bone. The mean age at diagnosis was 25 years, 39 (59%) were female, and the mean duration of follow‐up was 48 months. Six (11%) patients had monostotic disease, with the remaining 60 (89%) patients having the polyostotic form; 16 (24%) patients had McCune‐Albright syndrome. The most common presenting complaint was headache (59%), followed by hearing loss (29%). The most common exam finding was cosmetic deformity (50%). Cholesteatoma (3%) and spontaneous cerebrospinal fluid fistula (1.5%) were found in a small percentage. No patients had evidence of motor cranial neuropathy by history or physical examination. Conclusions The clinical presentation of fibrous dysplasia involving the temporal bone is variable. A growing number of patients are diagnosed incidentally through imaging, and since most patients experience a benign course, the majority can be followed clinically without need for intervention. Level of Evidence 4. Laryngoscope, 125:1438–1443, 2015